Investigating long period X-ray pulsars in the Large Magellanic Cloud - Vasilopoulos, Georgios (2018)
Long period pulsars (P> 1000 s) constitute a sub-population ofhigh-mass X-ray binaries. To date, only a few of these rare systems,which occupy the tail of the spin period distribution of X-ray pulsars,have been discovered. Nevertheless, their study offers unique insightsinto evolutionary scenarios of the high-mass X-ray binary population. Wepropose four XMM-Newton observations aiming at improving our understandingof long period pulsars. The proposed observations will be performedto two systems located in the LMC with known spin periods for studyingtheir spin evolution, and two new candidate long period pulsars in orderto increase the number of known systems.